Legal Certainty of Fixed-Term Work Agreements for Tourism Workers - I Gede Donny Mahendra; Styawati, Ni Komang Arini; Wiryani, Made (Universitas Bali Dwipa, 2025)
The objectives to be achieved in this study are to analyze the legal certainty of fixed-term employment agreements (PKWT) for workers in the tourism sector. The method used is normative juridical through literature review. The problems are: 1. How is the legal certainty regarding changes in the status of fixed-term employment agreements for workers who have passed a work period of 5 (five) years, 2. What legal remedies can be taken by workers and labor unions who do not receive their rights. The results of this study indicate that Law No. 6 of 2023 and PP No. 35 of 2021 still do not comprehensively regulate the work period and work status of PKWT workers. The existence of the Constitutional Court Decision Number 168/PUU-XXI/2023, one of the decisions of which emphasizes that the PKWT work period is 5 (five) years, is still unable to provide legal certainty for PKWT workers in terms of work status, if there is a violation of the work period by the company. There needs to be an explicit legal regulation regarding the work status of PKWT if it has passed a work period of 5 (five) years. Some legal efforts that can be done when workers do not get their rights are First, dispute resolution carried out through non-litigation channels where in this mechanism there are four types of settlements, namely bipartite, mediation, conciliation and arbitration. Second, litigation channels where in this mechanism through the industrial relations court.